2009
DOI: 10.1111/j.1365-2729.2009.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning projects – a critical analysis of the state of the art

Abstract: This paper provides a critical analysis of Mobile Learning projects published before the end of 2007. The review uses a Mobile Learning framework to evaluate and categorize 102 Mobile Learning projects, and to briefly introduce exemplary projects for each category. All projects were analysed with the criteria: context, tools, control, communication, subject and objective. Although a significant number of projects have ventured to incorporate the physical context into the learning experience, few projects inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
195
0
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(241 citation statements)
references
References 55 publications
2
195
0
13
Order By: Relevance
“…Considerando el incremento de la movilidad sufrido en las últimas décadas, tanto por razones profesionales y/o académicas como personales, el aprendizaje de lenguas se ha convertido en una de las líneas clave de nuestra sociedad para la inserción laboral, la promoción académica y el intercambio intercultural (Frohberg et al, 2009;Fisher y Baird, 2007). En este contexto, muchas de las iniciativas políticas europeas abogan desde hace años por: (1) hacer del aprendizaje permanente y de la movilidad una realidad; (2) mejorar la calidad y la eficiencia de la educación y la formación; (3) promover la equidad y la cohesión social; y (4) intensificar la creatividad, la innovación y la iniciativa empresarial (Official Journal of the European Communities, 2001/166, pp.…”
unclassified
“…Considerando el incremento de la movilidad sufrido en las últimas décadas, tanto por razones profesionales y/o académicas como personales, el aprendizaje de lenguas se ha convertido en una de las líneas clave de nuestra sociedad para la inserción laboral, la promoción académica y el intercambio intercultural (Frohberg et al, 2009;Fisher y Baird, 2007). En este contexto, muchas de las iniciativas políticas europeas abogan desde hace años por: (1) hacer del aprendizaje permanente y de la movilidad una realidad; (2) mejorar la calidad y la eficiencia de la educación y la formación; (3) promover la equidad y la cohesión social; y (4) intensificar la creatividad, la innovación y la iniciativa empresarial (Official Journal of the European Communities, 2001/166, pp.…”
unclassified
“…While the potential for innovation and pedagogical change afforded by mlearning is mooted by researchers, for example: (Cook 2010;Herrington et al 2009;Laurillard 2007;Kukulska-Hulme 2010), the evidence is often ephemeral (Pachler, Bachmair, and Cook 2010). In their review of 112 innovative mobile learning projects published between , Frohberg, Goth and Schwabe (2009 found that only 5% of these projects focused upon social learning, less than 4% required higher level thinking, with 89% targeting novice learners, and only 10% facilitated user-generated content. In contrast to the majority of mlearning projects, the researcher has been interested in transforming pedagogy from teacher-directed towards social constructivism using mlearning as a catalyst to enable student-generated content and student-generated learning contexts.…”
Section: Secrets Of Mlearning Failures: Confronting Reality Introductionmentioning
confidence: 99%
“…While the potential for innovation and pedagogical change afforded by mlearning is mooted by researchers, for example: (Cook 2010;Herrington et al 2009;Laurillard 2007;Kukulska-Hulme 2010), the evidence is often ephemeral (Pachler, Bachmair, and Cook 2010). In their review of 112 innovative mobile learning projects published between 2002, Frohberg, Goth and Schwabe (2009 found that only 5% of these projects focused upon social learning, less than 4% required higher level thinking, with 89% targeting novice learners, and only 10% facilitated user-generated content. In contrast to the majority of mlearning projects, the researcher has been interested in transforming pedagogy from teacher-directed towards social constructivism using mlearning as a catalyst to enable student-generated content and student-generated learning contexts.…”
Section: Introductionmentioning
confidence: 99%